2020
DOI: 10.2217/nmt-2020-0021
|View full text |Cite|
|
Sign up to set email alerts
|

Application of the ‘5-2-1’ Screening Criteria in Advanced Parkinson’s Disease: Interim Analysis of DUOGLOBE

Abstract: Aim: A Delphi expert consensus panel proposed that fulfilling ≥1 of the ‘5-2-1 criteria’ (≥five-times daily oral levodopa use, ≥two daily hours with ‘Off’ symptoms or ≥one daily hour with troublesome dyskinesia) suggests advanced Parkinson’s disease (PD). Patients & methods: DUOdopa/Duopa in Patients with Advanced PD – a GLobal OBservational Study Evaluating Long-Term Effectiveness (DUOGLOBE) – is a single-arm, postmarketing, observational, long-term effectiveness study of levodopa–carbidopa intestinal gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 36 publications
3
44
0
4
Order By: Relevance
“…presented a consensus statement of international experts that eventually led to the development of the so-called 5-2-1 criteria. [14,31] The 5-2-1 criteria were introduced to help general neurologists identify advanced PD patients who are possibly eligible for AT. [17] These criteria are easy to use and the name itself serves as a mnemonic device.…”
Section: Discussionmentioning
confidence: 99%
“…presented a consensus statement of international experts that eventually led to the development of the so-called 5-2-1 criteria. [14,31] The 5-2-1 criteria were introduced to help general neurologists identify advanced PD patients who are possibly eligible for AT. [17] These criteria are easy to use and the name itself serves as a mnemonic device.…”
Section: Discussionmentioning
confidence: 99%
“…The studies investigating different diagnostic tools for PD patients (n = 35) contributed to 23.48% of the research. The Romanian researchers participated in developing various clinical scales, including the non-motor symptoms scale (NMSS) [60,61], scales for outcomes in Parkinson's disease-cognition (SCOPA-COG) [62], King's Parkinson's disease scale [77] and King Parkinson's disease questionnaire [87], Parkinson's disease composite scale (PDCS) [90,92], and the "5-2-1" screening criteria for advanced PD [93]. Nonetheless, the number of neuroimaging studies is low (n = 3), and there is a lack of studies on other more expensive diagnostic tools (e.g., dopamine transporters imaging, DaTscan).…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review identified 35 studies investigating different diagnostic tools (Supplemental Material: Table S2). Among them, 13 [60,62,63,93]. The rest of 41 studies were performed in national settings.…”
Section: Studies On Diagnostic Tests In Parkinson's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…This has led to the development of the ‘5-2-1’ paradigm (≥5-times oral levodopa doses/day, ≥2 h of ‘off’ symptoms/day, ≥1 h of troublesome dyskinesia/day) to identify motor aspects of advanced PD and ensure timely referral for DAT initiation [ 10 ]. The interim analysis of DUOGLOBE, an observational study evaluating the long-term effectiveness of LCIG in patients with advanced PD, showed that only 20% of patients met all of the 5-2-1 criteria, but 98% met at least one criterion, highlighting the need for further refinement and personalisation of DAT selection [ 12 ].…”
Section: Advanced Parkinson’s Disease: the Clinical Scenariomentioning
confidence: 99%